Efficient ultra-high-voltage controller-based complementary-metal-oxide-semiconductor switched-capacitor DC-DC converter for radio-frequency micro-electro-mechanical systems switch actuation - Wong, Yan Chiew; Arslan, Tughrul S.; Erdogan, Ahmet T.; El-Rayis, Ahmed O. (IET, 2013)
Achieving wireless connectivity in ever smaller, lower power portable devices with increasing number of features and better radio-frequency (RF) performance is becoming difficult to fulfill through existing RF front-end technology. RF micro-electro-mechanical systems (MEMS) switch technology, which has significantly better RF characteristics than conventional technology and has near-zero power consumption, is one of the emerging solutions for next generation RF front-ends. However, to achieve satisfactory RF MEMS device performance, it is often necessary to have an actuating circuitry to generate high direct current (DC) voltages for device actuation with low power consumption. In this study, the authors present an RF MEMS switch controller based on a switched-capacitor (SC) DC-DC converter in a 0.35 μm CMOS technology. In this design, novel design techniques for a higher output voltage and lower power consumption in a smaller die area are proposed. The authors demonstrate the design of the high-voltage (HV) SC DC-DC converter by using low-voltage transistors and address reliability issues in the design. Through the proposed design techniques, the SC DC-DC converter achieves more than 25% higher boosted voltage compared to converters that use HV transistors. The proposed design provides 40% power reduction through the charge recycling circuit. Moreover, the SC DC-DC converter achieves 45% smaller than the area of the conventional converter.